Framework to Maintain Specialisations in a General Degrees Structure: An economical high-value degree structure - Tony de Souza-Daw; Ahmed Falah; Kiran Fahd; Sazia Parvin; Antony Di Serio (International Journal of Asian Education, 2022)
Structuring a degree is a common activity for course developers. Analyzing appropriate subjects and year levels, establishing pre- and co-requisite, and benchmarking against similar degrees are common academic activities. However, the degree structure itself has not had significant changes until now. A degree often lacks flexibility and cohesion and arguably may even lose the main concept of making students highly skilled in the selected labor market more employable. After examining different degree structures, approaches, and employability incentives, we identified a degree structure that can divide each subject into components. Subjects' learning activities, tutorials, and assessments are tailored to align more closely with employment skills. We then proposed breaking all subjects into components relative to year levels, such as majors, minors, streams, and more. This sub-division of work can be performed to any degree. Particular advantages come with a general degree with standard core units and majors—creating learning activities closer to the major and offering students a more robust academic scaffold of their subjects. In addition, higher Education providers benefit by having a cost-efficient degree with minimum overhead to pass the benefits onto students. We discussed several examples from engineering, business, and information technology. Showing how learning opportunities can be divided per degree and subjects into degrees, majors, streams, and specializations. Students studying this framework will have developed skills firmly built on each other, enabling specialization in employment careers and academically. Closing the gap between employment and graduation.